The neurodegenerative process in a neurotoxic rat model and in patients with Huntington's disease: histopathological parallels and differences - Gunčová, Ivana; Látr, Ivan; Mazurová, Yvona (Acta histochemica, 2011)
Although Huntington's disease (HD) occurs only in humans, the use of animal models is crucial for HD research. New genetic models may provide novel insights into HD pathogenesis, but their relevance to human HD is problematic, particularly owing to a lower number of typically degenerated and dying striatal neurons and consequent insignificant reactive gliosis. Hence, neurotoxin-induced animal models are widely used for histopathological studies. Unlike in humans, the neurodegenerative process (NDP) of the HD phenotype develops very fast after the application of quinolinic acid (QA). For that reason, we compared three groups of rats in more advanced stages (1-12 months) of the QA lesion with 3 representative HD cases of varying length and grade. The outcomes of our long-term histological study indicate that significant parallels may be drawn between HD autopsies and QA-lesioned rat brains (particularly between post-lesional months 3 and 9) in relation to (1) the progression of morphological changes related to the neuronal degeneration, primarily the rarefaction of neuropil affecting the density as well as the character of synapses, resulting in severe striatal atrophy and (2) the participation of oligodendrocytes in reparative gliosis. Conversely, the development and character of reactive astrogliosis is principally conditioned by the severity of striatal NDP in the context of neuron-glia relationship. Despite the above-described differences, morphological patterns in which the components of striatal parenchyma react to the progression of NDP are similar in both human and rat brains. Our study specifies the possibilities of interpreting the morphological findings gained from the QA-induced animal model of HD in relation to HD post-mortem specimens.
Keywords: Animals; Huntingtonova nemoc; degenerace nervu; Rats, Wistar; Gliosis; lidé; mozek; Oligodendroglia; oligodendroglie; Male; progrese nemoci; modely nemocí na zvířatech; Brain; Huntington Disease; Disease Progression; Disease Models, Animal; krysa rodu Rattus; Nerve Degeneration; zvířata; mužské pohlaví; glióza; Rats; potkani Wistar; Humans